Simplified domestic wastewater treatment system for vegetable crop irrigation - DA SILVA, Tamires Lima [UNESP]; Sánchez-Román, Rodrigo Máximo [UNESP]; Queluz, João Gabriel Thomaz [UNESP]; Pitoro, E Valdemiro Simão João (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2020)
In vegetable crop production the need for irrigation can be constant, and the water used must present good quality. After adequate treatment, domestic wastewater (DW) can be a viable and safe option of water for reuse. This work evaluated the efficiency of a simplified DW treatment system composed of a biological filter bed and a solar concrete disinfection reactor for reuse in vegetable crop irrigation. The system was installed at the School of Agronomic Science-FCA, Unesp, Botucatu-SP. In the reactor, depths of 10, 15 and 20 cm were tested. The solar disinfection in the reactor resulted in a treated effluent with quality in accordance with the threshold established by the World Health Organization for unrestricted irrigation (fecal coliforms ≤ 1,000 NMP 100 mL-1 ) after four hours of solar exposure. Considering pH, EC and TDS parameters, the DW treated can be classified as “none restriction” use for irrigation according to the classification proposed by FAO. With the average results of N, P and K concentrations in the treated DW, its nutritional potential for vegetable crop production was estimated as: 525.6 kg m3 ha-1 year-1 to N, 175.2 kg m3 ha-1 year-1 to P and 521.9 kg m3 ha-1 year-1 to K.
Sistema simplificado de tratamento de água residuária doméstica para irrigação de hortaliças
Keywords: Agricultural reuse; Biological filter bed; Sewage; Solar disinfection